Difficulties in implementing 21st century skills competence in vocational education learning - Farid Mutohhari; S. Sutiman; Muhammad Nurtanto; Nur Kholifah; Achmad Samsudin (Institute of Advanced Engineering and Science, 2021)
The 21st century learning requires complex competencies, transformations of technology-based learning and non-cognitive skills need. This situation makes it difficult for teachers of Indonesian vocational education apply 21st century skills. This study aimed to analyze the level of difficulty of teachers and students in vocational education and analyzing the differences in the difficulties faced in vocational education. This research used survey research with a quantitative approach. A total of 178 people participated in the study consisting of two public vocational high schools and two private vocational schools with the distribution of respondents consisting of 155 students and 23 teachers. Collecting data using a questionnaire in the form of a statement of difficulties faced by teachers and students, including creativity skills, critical thinking, problem solving, communication, collaboration, and digital literacy or information and communication technology (ICT) as many as 50 items. The instrument used was a Likert scale with very difficult, difficult, easy, and very easy categories. The findings of the study showed: i) All skills were identified on the “easy” criteria; and ii) There were significant differences between the difficulties faced by teachers and students, especially communication skills. The recommendation in this study is the need to improve 21st century skills to produce competitive graduate candidates in vocational education.